A review of research on agrivoltaic systems. (June 2022) - Mamun, Mohammad Abdullah Al; Dargusch, Paul; Wadley, David; Zulkarnain, Noor Azwa; Aziz, Ammar Abdul
Abstract: The expansion of large-scale photovoltaic (PV) power generation is essential to global efforts to mitigate climate change. A constraint to such PV development is its extensive space requirements, complicated by increasing competition for land driven by population growth and rising food demand. Agrivoltaic systems, which integrate crop production and PV power generation, offer a potential solution to the land economy problem. In this article, we present the results of a systematic review of agrivoltaic research backed with relevant analysis, discussion, and directions for future research. In total, 98 studies were appraised. Among them, 48 dealt with specific applications, while 50 were preoccupied with the scale of PV production. Fourteen of those 50 inquiries examined small-scale (<100 kW) PV systems. The remaining 36 addressed medium-to-large-scale facilities (over 100 kW), with 26 oriented to installations exceeding MW in capacity. Apart from originating mainly in the northern hemisphere, research characteristically focusses on engineering issues – either configuration, or factors influencing power yield. Currently lacking is a comprehensive financial performance model for agrivoltaic systems. Further, very little investigation has been directed to large-scale (>1.0 MW) facilities which integrate livestock grazing. These later issues constitute important gaps in our knowledge because the regions around the world with the greatest potential for PV power generation are typically those where grazing is prominent. Highlights: A systematic review on agrivoltaic research involving crop and energy production. Most of the studies (83 out of 98) were carried out in nine countries. Key issues are shading and microclimatic conditions under the solar panels. Social impacts include creation of new jobs, community income and tax revenues. Priority areas for future research on agrivoltaics have been identified.